The N-terminal portion of autoinhibitory element modulates human endothelial nitric-oxide synthase activity through coordinated controls of phosphorylation at Thr(495) and Ser(1177) - Wu, Pei-Rung (Portland Press Ltd., 2014)
NO production catalysed by eNOS (endothelial nitric-oxide synthase) plays an important role in the cardiovascular system. A variety of agonists activate eNOS through the Ser(1177) phosphorylation concomitant with Thr(495) dephosphorylation, resulting in increased ·NO production with a basal level of calcium. To date, the underlying mechanism remains unclear. We have previously demonstrated that perturbation of the AIE (autoinhibitory element) in the FMN-binding subdomain can also lead to eNOS activation with a basal level of calcium, implying that the AIE might regulate eNOS activation through modulating phosphorylation at Thr(495) and Ser(1177). Here we generated stable clones in HEK-293 (human embryonic kidney 293) cells with a series of deletion mutants in both the AIE (Δ594–604, Δ605–612 and Δ626–634) and the C-terminal tail (Δ14; deletion of 1164–1177). The expression of Δ594–604 and Δ605–612 mutants in non-stimulated HEK-293 cells substantially increased nitrate/nitrite release into the culture medium; the other two mutants, Δ626–634 and Δ1164–1177, displayed no significant difference when compared with WTeNOS (wild-type eNOS). Intriguingly, mutant Δ594–604 showed close correlation between Ser(1177) phosphorylation and Thr(495) dephosphorylation, and NO production. Our results have indicated that N-terminal portion of AIE (residues 594–604) regulates eNOS activity through coordinated phosphorylation on Ser(1177) and Thr(495).